Nationalism on Social Media: The impacts of comments on ASEAN Football Pages on mental health - Rangga Cipta Perdana; Genta Iverstika Gempita (GHMJ (Global Health Management Journal), 2024)
Background: As a modern communication medium, Facebook provides a new place to people who live far apart to interact and discuss on the same topic, such as football. This research examines how the nationalism is generated through Facebook. From the perspective of social realities, Facebook is observed as a channel of communication utilized by football lovers. However, communication through Facebook also causes conflicts among its users.